2023
DOI: 10.1111/nph.18914
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐based assembly of arbuscular mycorrhizal fungal communities determines soil carbon formation and retention

Abstract: Fungi are crucial for soil organic carbon (SOC) formation, especially for the more persistent mineral-associated organic C (MAOC) pool. Yet, evidence for this often overlooks arbuscular mycorrhizal fungi (AMF) communities and how their composition and traits impact SOC accumulation.We grew sudangrass with AMF communities representing different traits conserved at the family level: competitors, from the Gigasporaceae family; ruderals, from the Glomeraceae family; or both families combined. We labeled sudangrass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 77 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Several recent studies demonstrate that additional soil physicochemical properties not included in this study, especially exchangeable Ca and Fe‐ and Al‐hydroxides, are better predictors of MAOC storage than % sand alone (King et al., 2023; Kirsten et al., 2021; Rowley et al., 2021). Microbial traits including mycorrhizal type (Craig et al., 2018; Horsch et al., 2023; Keller et al., 2021) and transformation efficiency may be additional modulators of both SOC fraction storage and f MAOC , though the majority of studies on microbial transformations have focused primarily on their effects on microbial‐derived MAOC (e.g., Craig et al., 2022; Ernakovich et al., 2021; Kallenbach et al., 2016; Liang et al., 2019). While satellite‐based NPP data is often used as a proxy for C inputs to the soil (e.g., Chen et al., 2021; Eclesia et al., 2016; He et al., 2023), it may not be as applicable to agricultural systems, where depending on management strategy, plant residues are often removed from the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies demonstrate that additional soil physicochemical properties not included in this study, especially exchangeable Ca and Fe‐ and Al‐hydroxides, are better predictors of MAOC storage than % sand alone (King et al., 2023; Kirsten et al., 2021; Rowley et al., 2021). Microbial traits including mycorrhizal type (Craig et al., 2018; Horsch et al., 2023; Keller et al., 2021) and transformation efficiency may be additional modulators of both SOC fraction storage and f MAOC , though the majority of studies on microbial transformations have focused primarily on their effects on microbial‐derived MAOC (e.g., Craig et al., 2022; Ernakovich et al., 2021; Kallenbach et al., 2016; Liang et al., 2019). While satellite‐based NPP data is often used as a proxy for C inputs to the soil (e.g., Chen et al., 2021; Eclesia et al., 2016; He et al., 2023), it may not be as applicable to agricultural systems, where depending on management strategy, plant residues are often removed from the soil.…”
Section: Discussionmentioning
confidence: 99%
“…There has been limited testing of the importance of hyphal density as of yet, but current evidence suggests hyphal density may be particularly important for stable SOM formation in AM and N-rich systems but may reduce MAOM formation in ECM systems (Hicks Pries et al, 2023;Horsch et al, 2023;Zhu, Zhang, et al, 2022). Whalen et al (2024) comprehensively tested whether a suite of soil fungal traits are linked to SOM formation potential and found that the formation of stable, chemically diverse SOM fractions was promoted by "multifunctional" species with intermediate investment across a group of traits (i.e., CUE, growth rate, turnover rate, and biomass protein and phenol contents), emphasizing the importance of trait synergies.…”
Section: 1029/2023jg007964mentioning
confidence: 99%
“…This relationship may have been established since plants first conquered the land 2 , and there is evidence showing that AMF improve plant growth and ecosystem productivity 3 . More recently, it was also reported that these symbionts can retain atmospheric carbon, indicating these play a significant role in the global climate balance 4,5 . Nonetheless, despite their relevance for plant fitness and long-term evolution, AMF show low morphological variability with no apparent plant specificity 6 .…”
Section: Introductionmentioning
confidence: 98%